Restrição calórica e extrato de Spirulina platensis frente ao íon ferroso no envelhecimento de Saccharomyces cerevisiae deletada ao gene sir2 - Benetti, Fábia (2013)
The aging process is accompanied by changes in the activity of cells, tissues and organs. The progressive accumulation of these changes has been associated with an imbalance in the homeostasis of the organism in relation to certain metals, with emphasis on ferrous ion, configured in the evolution of neurodegenerative diseases. The use of antioxidant therapies may interfere with this process, reducing oxidative stress and damage caused by the accumulation of ferrous ions (Fe²+). The cyanobacterium Spirulina platensis stands out for having functional properties as natural antioxidant, found in models in vivo and in vitro. The caloric restriction (CR) has been identified with potential to reduce or retard diseases associated with aging, as well as extending the life span in different experimental models. Its benefits can be related to the activation of gene induction Silent Information Regulator 2 (SIR2). We seek to evaluate the potential of the extract of Spirulina platensis and RC in Saccharomyces cerevisiae cells, subjected to Fe²+. Strains of S. cerevisiae, control (WT) and deleted the SIR2 gene (sir2Δ) were cultured in standard medium (YPD 2% glucose) and on caloric restriction (YPD 0.5% glucose). These strains were further exposed or not exposed to 1mM Fe²+ and 0.8 mg / ml of extract from Spirulina platensis during and after 1h underwent a non proliferating (sterile distilled water, temperature of 37 º C for 24 h), this situation, which characterized the cellular aging. Cells were collected for analysis of cell survival by plating and lipid peroxidation by the method TBARS (thiobarbituric acid reactive substances) before aging time (1 h) and after aging (time 24 h). The results show that cell survival was reduced in the absence of sir2Δ. This effect was demonstrated significantly (p <0.05) before aging for treatments pattern, RC and RC + Fe2+ and after aging, this same effect was observed for treatments pattern Extract Spirulina platensis, RC, Extrac Spirulina platensis + Fe²+, Fe²+ + RC. The results for lipid peroxidation demonstrate that deletion of sir2Δ increased levels of malonaldehyde (MDA). This effect was significant (p <0.05) before and after aging for all treatments, except for the standard treatment time of 1 hour. In this context, we conclude that the gene deletion sir2Δ decreases cell survival and increased lipid peroxidation for all treatments. Although we conclude that antioxidant therapies (RC and extract of Spirulina platensis) showed a protective effect on the toxicity induced by ferrous ion (Fe²+) for both WT cells, as for sir2Δ, with significant results (p <0.05 ) increase in cell survival and reduction in lipid peroxidation.